Informatics-enabled citizen science to advance health equity. (21st June 2021) - Valdez, Rupa S; Detmer, Don E; Bourne, Philip; Kim, Katherine K; Austin, Robin; McCollister, Anna; Rogers, Courtney C; Waters-Wicks, Karen C
Abstract: The COVID-19 pandemic has once again highlighted the ubiquity and persistence of health inequities along with our inability to respond to them in a timely and effective manner. There is an opportunity to address the limitations of our current approaches through new models of informatics-enabled research and clinical practice that shift the norm from small- to large-scale patient engagement. We propose augmenting our approach to address health inequities through informatics-enabled citizen science, challenging the types of questions being asked, prioritized, and acted upon. We envision this democratization of informatics that builds upon the inclusive tradition of community-based participatory research (CBPR) as a logical and transformative step toward improving individual, community, and population health in a way that deeply reflects the needs of historically marginalized populations.